Brazil's offshore wind energy potential assessment based on a Spatial Multi-Criteria Decision Analysis. (August 2021) - Vinhoza, Amanda; Schaeffer, Roberto
Abstract: Brazil is an emerging market for offshore wind energy, with its first projects having already applied for environmental permits. However, few studies have actually evaluated Brazil's offshore potential, and those analyses have focused on its gross resource potential. This paper thus aims to assess Brazil's offshore wind potential through a novel approach that allows for the evaluation and mapping of the potential in different levels (Gross, Technical and Environmental and Social) and highlights the most economically attractive areas for offshore wind deployment, following a Spatial Multi-Criteria Decision Analysis. Results for Brazil show 1688 GW of Gross Potential, 1064 GW of Technical Potential and 330 GW of Environmental and Social Potential. The least economically attractive areas are mainly in the Southeast region, while the most attractive ones are concentrated in the Northeast region. The top ten areas for offshore development are also highlighted, totaling 126 GW of capacity. In short, this paper addresses the knowledge gap towards a comprehensive potential assessment for Brazil and concludes that the country has a significant offshore wind potential that can be sustainably deployed if proper siting criteria are applied. The approach proposed here is replicable and capable of informing the planning of sustainable offshore wind development in other regions or countries. Highlights: Brazil's Gross, Technical, and Environmental-Social Offshore Wind Potentials. GIS approach considers offshore wind farms siting constraints to map suitable areas. GIS-MCDA to rank suitable areas according to their economic attractiveness. Environmentally and socially suitable areas sum 330 GW of potential capacity. The top 10 most attractive areas in Brazil sum 126 GW of potential capacity.